The Effects of Porphyromonas gingivalis on Atherosclerosis-Related Cells - Zhang, Jiaqi; Xie, Mengru; Huang, Xiaofei; Chen, Guangjin; Yin, Ying; Lu, Xiaofeng; Feng, Guangxia; Yu, Ran; Chen, Lili (Frontiers in Immunology, 2021)
Atherosclerosis (AS), one of the most common types of cardiovascular disease, has initially been attributed to the accumulation of fats and fibrous materials. However, more and more researchers regarded it as a chronic inflammatory disease nowadays. Infective disease, such as periodontitis, is related to the risk of atherosclerosis. Porphyromonas gingivalis (P. gingivalis), one of the most common bacteria in stomatology, is usually discovered in atherosclerotic plaque in patients. Furthermore, it’s reported that P. gingivalis can promote the progression of atherosclerosis. Elucidating the underlying mechanisms of P. gingivalis in atherosclerosis attracted attention, which is thought to be crucial to the therapy of atherosclerosis. Nevertheless, the pathogenesis of atherosclerosis is much complicated, and many kinds of cells participate in it. By summarizing existing studies, we find that P. gingivalis can influence the function of many cells in atherosclerosis. It can induce the dysfunction of endothelium, promote the formation of foam cells, as well as the proliferation and calcification of vascular smooth muscle cells, lead to the imbalance of regulatory T cells (Tregs) and T helper (Th) cells, ultimately promoting the occurrence and development of atherosclerosis. This article summarizes the specific mechanism of atherosclerosis caused by P. gingivalis. It sorts out the interaction between P. gingivalis and AS-related cells, which provides a new perspective for us to prevent or slow down the occurrence and development of AS by inhibiting periodontal pathogens.